Effect of substrate bias voltage on the microstructural and mechanical properties of tin-coated HSS synthesized by capvd technique - Ali, Mubarak; Hamzah, Esah; Mohd Toff, Mohd Radzi (World Scientific, 2006)
Titanium nitride (TiN) films were deposited on high-speed steel (HSS) using cathodic arc physical vapor deposition (CAPVD) technique. The effect of substrate bias on the crystallography, microstructure, deposition rate, coating thickness and composition, hardness, and adhesion strength of TiN films was investigated. The crystallography of the films was investigated using X-ray diffraction with glazing incidence angle technique. The coating microstructure and elemental composition analysis were carried out using field emission scanning electron microscopy (FE-SEM) together with energy-dispersive X-ray. Crystallography of the films revealed that the effect of substrate bias shows complex symmetry in crystal structure. The resputtering effect due to the high-energy ion bombardment on the film surface influenced the thickness as well as the color of deposited coatings. By increasing the substrate bias from 0 to - 150 V, the size and amount of macrodroplets decreased, whereas the micro-Vickers hardness decreased from 2530 HV0.05 to 1500 HV0.05. Scratch tester used to compare the critical loads for coatings and the adhesion achievable at substrate bias of - 50 V was demonstrated, with relevance to the various modes.